Poor through-put rates of distance learners in computing courses: Is continuous assessment the answer? - Home, T.; Naude, E. (South African Journal of Higher Education, 2007)
Teaching computer programming through distance education is not easy. The through-put rate of students in computing courses at tertiary distance learning institutions is generally poor. This article forms part of a long-term project investigating ways in which this situation could be improved. In this article, we investigate the extent to which students' commitment to continuous assessment affects their examination results. A summary of research results on the relationship between the examination pass rate and the continuous assessment performance of students during the academic year is given. We also investigate the effect that the introduction of a continuous assessment mark (a year mark) that counts towards the final mark of a student has on the through-put rate. Although this study involved only computing courses, the results may be relevant and of interest to lecturers and researchers in related disciplines such as mathematics, decision sciences and physics.